Help for Spain! (circular) - Citrine, Walter, 1887-1983
018a-0026-001 Telegraphic Address TRADUNIC, SOWEST, LONDON Telephone: VICTORIA 6261 (4 lines) The TRADES UNION CONGRESS GENERAL COUNCIL TRANSPORT HOUSE, SMITH SQUARE, LONDON. S.W.1. General Secretary: SIR WALTER CITRINE, K.B.E. (To whom all communications should be addressed) Your Ref: Our Ref: WMC/HVT/FC/871. Department: Secretary's. In reply please quote:- CIR. NO. 140. (1935-36). 10th August, 1936. TO SECRETARIES OF ALL AFFILIATED UNIONS. Dear Sir (Madam), HELP FOR SPAIN ! In connection with the above matter we have pleasure in reporting that the Fund to date totals £5,400. Many affiliated Unions have already made preliminary donations to the Fund, although in the majority of cases it has not yet been possible to place the matter before the respective Executives. It is sincerely hoped that in all cases there will be a generous response to the appeal. We have received a communication from the International Federation of Trade Unions, in the course of which it is stated that although they are convinced that, up till now, no material of war has been sent to the Spanish rebels from countries where there are free Trade Unions, they would urge affiliated and friendly organisations to keep particularly on the alert, in view of the fact that the Fascist States and Parties will do all they can, not only to give direct help to the rebels, but also to order or obtain material of war indirectly from other countries, and to transport it across other countries. Further, the International Federation of Trade Unions request their affiliated bodies to use all means at their command to reveal any manoeuvres of this description. It is known that the International Transportworkers' Federation have communicated with their affiliated Organisations on this matter, but the General Council would be glad (if your members are concerned with the manufacture or transport of munitions) if you would take such action as may be necessary to secure and forward to us timely information of such orders or consignments as may be viewed with suspicion having the above points in mind. It will be known that munitions can only leave this country by licence granted by the Government, and if information can be supplied on the lines suggested above it will enable the General Council to keep a check on the matter. Yours sincerely, WALTER CITRINE, General Secretary. 292/946/18a/26